Targeted therapy of non-small-cell lung carcinoma - Divya Tiwari; Seth A. Brodie; Johann C. Brandes (Therapeutic Advances in Respiratory Disease, 2012)
The rapid expansion of novel technologies in cancer research over the past several years has led to a dramatically improved understanding of the molecular biology of lung cancer. As a consequence, novel targeted therapies are rapidly being developed. In this review, we summarize the most important molecular pathways in lung cancer and describe the clinical evidence for the development of therapies against these targets.